MECHANICAL INTERACTIVE E-BOOK (MAIBOOK) LEARNING MEDIA DEVELOPMENT IN MACHINE ELEMENTS COURSE - Hamzah, Bahha; Hamdani, Aam; Komaro, Mumu (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
Abstract: Learning with verbal media and writing the material on white boards can make students feel bored, so it is necessary to insert learning media that utilize technological developments to streamline the learning process. The purpose of this research is to create an interactive e-book-based learning media in the machine element course and try it out in learning. This study uses the ADDIE research model, namely analysis, design, development, implementation and evaluation. Based on the research conducted, it can be concluded that the results of the developed learning media product, namely Mechanical Interacrive E-Book (MAIBOOK) in the machine element course made with the help of Kotobee Author software and can be read on electronic devices such as smartphones and computers. The results of the media expert's validation of the developed MAIBOOK learning media got a good category. The results of the material expert's validation of the MAIBOOK learning media that was developed got a very good category. Student responses to the developed learning media products get a percentage of 85.3%. So that the response of students is categorized as very good.Keywords: Learning media, Machine elements, ADDIE research methodology, E-book, Interactive e-bookAbstrak: Pembelajaran dengan media verbal dan menulis materi di white board dapat membuat peserta didik merasa bosan, sehingga perlu menyisipkan media pembelajaran yang memanfaatkan perkembangan teknologi guna menefektifkan proses pembelajaran. Tujuan dari penelitian ini adalah membuat media pembelajaran berbasis interactive e-book pada matakuliah elemen mesin dan menguji cobanya dalam pembelajaran. Penelitian ini menggunakan model penelitian ADDIE yaitu analisis (analysis), desain (design), pengembangan (development), implementasi (implementation) dan evaluasi (evaluation). Berdasarkan penelitian yang dilakukan, dapat disimpulkan bahwa, hasil produk media pembelajaran yang dikembangkan yaitu Mechanical Interacrive E-Book (MAIBOOK) pada matakuliah elemen mesin dibuat dengan bantuan software Kotobee Author dan dapat dibaca pada perangkat elekronik seperti smartphone dan komputer. Hasil Validasi ahli media terhadap media pembelajaran MAIBOOK yang dikambangkan mendapat kategori baik. Hasil Validasi ahli materi terhadap media pembelajaran MAIBOOK yang dikambangkan mendapat kategori sangat baik. Respon peserta didik terhadap produk media pembelajaran yang dikembangkan mendapatkan persentase sebesar 85.3%. Sehingga respon peserta didik dikategorikan sangat baik. Kata kunci: Media pembelajaran, Elemen mesin, Metodelogi penelitian ADDIE, E-book, Interactive e-book.